CHARACTERIZATION AND NARRATIVE STRUCTURE IN COVERING GOVERNMENT CRITICISMS ON ONLINE MEDIA - Asyhab Arno Wijaya; Turnomo Rahardjo (UNIVERSITAS PAKUAN, 2022)
It has been two years since the global community has lived side by side with the Covid-19 pandemic. Covid-19 itself has had a significant impact on world life, including restrictions on social activities and the decline in people's purchasing power due to the economic effects caused by the pandemic. In the midst of the crush of the two effects caused by this pandemic, there is anxiety in the community. This growing anxiety is then channeled in various forms, both online and offline. Offline this unrest has turned into murals that are critical of the government. This study aims to analyze the structure of the narrative and its characterization in a news report about the mural criticism of the government. This research is a qualitative research with the method of collecting data from online documentation studies on news published by Kompas, Tribunnews, and Detik within a certain time span. The theory used in this study is Greimas's Narrative Theory where it is stated that in the narrative text there are six actors who can help to see how the structure and characterization in the narrative text. The results of this study indicate that the media places mural artists, law enforcement officers, murals, and people's aspirations in different characterizations and the writing of the narrative text can be easily understood by the readers.